Trichopilia x ramonensis (Orchidaceae), un híbrido natural de Costa Rica - Morales, Carlos O. (2016)
The natural hybrid Trichopilia x ramonensis (T. marginata x T. suavis) from the San Ramón region of Costa Rica is here described and illustrated. The name of this hybrid was used for the first time in 1992, nevertheless it has so far not been validly published.